A Study of Cosmopolitanism in the Movie Screenplay of Ocean’s Eleven - Abdillah, Michael Fadlan (Journal of Literature, Linguistics, & Cultural Studies, 2023)
Globalization has become a primary concern today, leading to significant shifts in social relations and making various global issues more visible. It is characterized by conditions where one can move easily from one place to another. Thus, it blurs the meaning of one's identity and citizenship. Hence, this research uses a structuralist approach and cosmopolitanism. The object of this research is Ocean's Eleven movie script which contains similar issues. The aim is to discover how cosmopolitanism is represented in Ocean's Eleven movie script and to find what kinds of cosmopolitanism are experienced by Ocean's Eleven characters. The researcher used the structuralism approach, Stuart Hall's concept of representation, cosmopolitan identity, and imaginative cosmopolitanism. Then by applying literary criticism, the researcher found that the representation of cosmopolitanism in Ocean's Eleven movie script is shown through character, dialogue, and narration. In addition, the cosmopolitanism shown by the characters of Ocean's Eleven is included in cultural cosmopolitanism. Based on the results, this research can be used as a model for further researchers in finding cosmopolitanism issues in literary works.